Induced maturation of human immunodeficiency virus - Mattei, Simone; Anders, Maria; Konvalinka, Jan; Kräusslich, Hans-Georg; Briggs, John A G; Müller, Barbara (Journal of virology, 2014)
UNLABELLED: HIV-1 assembles at the plasma membrane of virus-producing cells as an immature, noninfectious particle. Processing of the Gag and Gag-Pol polyproteins by the viral protease (PR) activates the viral enzymes and results in dramatic structural rearrangements within the virion--termed maturation--that are a prerequisite for infectivity. Despite its fundamental importance for viral replication, little is currently known about the regulation of proteolysis and about the dynamics and structural intermediates of maturation. This is due mainly to the fact that HIV-1 release and maturation occur asynchronously both at the level of individual cells and at the level of particle release from a single cell. Here, we report a method to synchronize HIV-1 proteolysis in vitro based on protease inhibitor (PI) washout from purified immature virions, thereby temporally uncoupling virus assembly and maturation. Drug washout resulted in the induction of proteolysis with cleavage efficiencies correlating with the off-rate of the respective PR-PI complex. Proteolysis of Gag was nearly complete and yielded the correct products with an optimal half-life (t(1/2)) of ~5 h, but viral infectivity was not recovered. Failure to gain infectivity following PI washout may be explained by the observed formation of aberrant viral capsids and/or by pronounced defects in processing of the reverse transcriptase (RT) heterodimer associated with a lack of RT activity. Based on our results, we hypothesize that both the polyprotein processing dynamics and the tight temporal coupling of immature particle assembly and PR activation are essential for correct polyprotein processing and morphological maturation and thus for HIV-1 infectivity. IMPORTANCE: Cleavage of the Gag and Gag-Pol HIV-1 polyproteins into their functional subunits by the viral protease activates the viral enzymes and causes major structural rearrangements essential for HIV-1 infectivity. This proteolytic maturation occurs concomitant with virus release, and investigation of its dynamics is hampered by the fact that virus populations in tissue culture contain particles at all stages of assembly and maturation. Here, we developed an inhibitor washout strategy to synchronize activation of protease in wild-type virus. We demonstrated that nearly complete Gag processing and resolution of the immature virus architecture are accomplished under optimized conditions. Nevertheless, most of the resulting particles displayed irregular morphologies, Gag-Pol processing was not faithfully reconstituted, and infectivity was not recovered. These data show that HIV-1 maturation is sensitive to the dynamics of processing and also that a tight temporal link between virus assembly and PR activation is required for correct polyprotein processing.
Keywords: uvolnění viru z buňky; Virology; sestavení viru; Human Immunodeficiency Virus Proteins; Humans; Proteolysis; Protein Processing, Post-Translational; HIV-1; lidé; proteolýza; Virus Release; proteiny viru HIV; virologie; posttranslační úpravy proteinů; Virus Assembly